A circuit analysis of a flux pump. (7th October 2019) - Campbell, Archie
Abstract: Flux pumps have been investigated for a number of years as a means of powering large magnets. In this paper a simple system consisting of one, or two, loops under a moving magnet is analysed theoretically. It is a circuit model using only Faraday's law of induction and the V – I characteristic. However in contrast to distributed systems with tapes or sheets, the performance can be calculated from first principles and the results expressed in a few simple formulae. With one loop and a constant I c no significant flux pumping occurs if the n value is large. However if I c is a function of B the saturation current is approximately I c1 – I c 2 where these are the critical currents in zero field and under the magnet respectively. Nearly all the magnet flux is transferred in each cycle so the number of cycles needed to reach saturation is about 2( I c1 – I c 2 ) L 2 / ϕ where L 2 is the inductance of the load magnet and ϕ the flux of the moving magnet. The loss is ϕI c joules on each pass and the mean loss about ϕI c /T watts, where T is the time of a pass. Adding another loop makes an even better flux pump even if I c is constant. Now the saturation current is I c and the number of cycles about 2 I c L 2 /ϕ . If the current starts above the saturation value it decreases to saturation over a similar number of cycles, more of a 'flux suck' than a flux pump.